PRAGMATIC FOUNDATIONS OF TEACHING THE KARAKALPAK LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article deals with the issues of teaching the Karakalpak language in educational institutions where education is conducted in other (foreign) languages, as well as the development of students’ language competencies is described.